Lessons for molecular diagnostics in oncology from the Cancer Research UK Stratified Medicine Programme. (April 2015) - Lindsay, Colin R; Shaw, Emily; Walker, Ian; Johnson, Peter WM
<x xml:space="preserve">Abstract</x> The implementation of stratified medicine in modern cancer care presents substantial opportunity to refine diagnosis and treatment but also numerous challenges. Through experience in a UK tumor profiling initiative, we have gained valuable insights into the complexities and possible solutions for routine delivery of stratified cancer medicine.